The influence of coping and social support on resilience among Indonesian adolescents with bullying victimization: Pengaruh koping dan dukungan sosial terhadap resiliensi remaja Indonesia korban bullying - Wildan Akasyah; Yohanes Andy Rias; Dang Thi Thuy My (Holistic Nursing Plus, 2023)
(1) Background: Bullying victims and their relationship to coping and social support in adolescents has been extensively discussed. However, little is established about the underlying this relationship, particularly the significance of resilience. We investigated the relations between coping and social support on resilience among Indonesian adolescents with bullying victimization; (2) Methods: A Cross-sectional study with 107 adolescents with bullying victims from a public school and two private schools in grades 7 to 9 was recruited. Adjusted coefficients β and 95% confidence interval were estimated using multiple linear regression; (4) Results: The findings indicated that coping was independently associated with resilience. Moreover, social support-friend was prominent factors on resilience. However, no significant relationship between social support-family and resilience among adolescents with bullying victims after controlling for confounding factors; (4) Conclusion: The study found that coping and social support-friends are strengthening determinants, particularly those aimed at improving resilience among adolescents with bullying victims.